ESTRO-EANO guideline on target delineation and radiotherapy details for glioblastoma - Niyazi, Karim-Maximilian; Andratschke, Nicolaus; Bendszus, Martin; Chalmers, Anthony J; Erridge, Sara C; Galldiks, Norbert; Lagerwaard, Frank J; Navarria, Pierina; Munck af Rosenschöld, Per; Ricardi, Umberto; van den Bent, Martin J; Weller, Michael; et al. (Radiotherapy and oncology, 2023)
Background and Purpose - Target delineation in glioblastoma is still a matter of extensive research and debate. This guideline aims to update the existing joint European consensus on delineation of the clinical target volume (CTV) in adult glioblastoma patients. - Material and Methods - The ESTRO Guidelines Committee identified 14 European experts in close interaction with the ESTRO clinical committee and EANO who discussed and analysed the body of evidence concerning contemporary glioblastoma target delineation, then took part in a two-step modified Delphi process to address open questions. - Results - Several key issues were identified and are discussed including i) pre-treatment steps and immobilisation, ii) target delineation and the use of standard and novel imaging techniques, and iii) technical aspects of treatment including planning techniques and fractionation. Based on the EORTC recommendation focusing on the resection cavity and residual enhancing regions on T1-sequences with the addition of a reduced 15 mm margin, special situations are presented with corresponding potential adaptations depending on the specific clinical situation. - Conclusions - The EORTC consensus recommends a single clinical target volume definition based on postoperative contrast-enhanced T1 abnormalities, using isotropic margins without the need to cone down. A PTV margin based on the individual mask system and IGRT procedures available is advised; this should usually be no greater than 3 mm when using IGRT.
Online verfügbar 13. April 2023, Artikelversion 21. April 2023
Gesehen am 15.06.2023